Pola Asuh Orang Tua dalam Mengembangkan Interaksi Sosial Anak Tunagrahita Sedang di SLB N 02 Padang - Temo, Anggi Loren; Marlina, Marlina (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
This research discusses about parenting parents in developing social interactions of moderate mentally retarded children in SLB N 02 Padang, where there is a moderate mentally retarded child has a good social interactions ability. This research goals to describe the form of parenting parents that able to develop their children?s social interctions that has a level of intelligence below the average so that the child has difficulty in interacting socially towards the social environtment so that later it can be used as motivation to every parent in giving the righ form of parenting parent for their children this research using qualitative desciptive, the subjects of this research are parent of children, his brother, local society, and teacher. So that all data can be collected by researcher using observation, interviews, and documentation. The result of researchis the parent have authoritative parenting type, wherethe parents have openness and create a good communication to their child so that make the child?s interactions social become good and able to get along with teh environtment.